The Desirability of Legal Rights for Novel Beings - Jowitt, Joshua (Cambridge quarterly of healthcare ethics, 2021)
The debate around whether novel beings should be legally recognized as legitimate rights holders is one that has produced a vast amount of commentary. This paper contributes to this discourse by shifting the normative focus of moral rights away from criteria possessed by the novel beings in question, and back toward the criterion upon which we ourselves are able to make legitimate rights claims. It draws heavily on the moral writing of Alan Gewirth’s identification of noumenal agency as the source of all legitimate rights claims. Taking Gewirthian ethical rationalism as providing a universally applicable hypothetical imperative which binds all agents to comply with its requirements, the paper argues that it is at least morally desirable that any legal system should recognize the moral rights claims of all agents as equally legitimate. By extension, it is at least morally desirable that the status of legal personhood should be granted by a legal system to all novel beings who are noumenal agents, insofar as this status is necessary for rights’ legal recognition. Having established the desirability of this extension, the paper closes with an examination of recent cases involving both biological and nonbiological novel beings in order to assess their conformity with the desirable approach outlined above. The paper demonstrates that such recognition is conceptually possible, thus requiring us to move beyond the current anthropocentricity of legal systems and recognize the legitimate moral claim for legal personhood for all novel beings who possess noumenal agency.